Opinions of forensic schizophrenia patients on the use of restraints: controversial Legislative - Margetić, Branimir (Array, 2014)
The use of restraints is a controversial issue even though legal regulations may seem straightforward. Our aims were to evaluate the forensic patients’ opinions on certain aspects of restraining and to compare these opinions with the current legal norms. Inpatients with schizophrenia or schizoaffective disorder at the Department of Forensic Psychiatry in Popovacˇa, Croatia, were asked the following questions about the use of mechanical restraints: (a) Should the patients’ family be informed about the use of restraints? (b) Should the physician ask the patient whether to inform the family about the use of restraints? (c) Can the use of restraints be a kind of punishment for intentionally aggressive behavior toward people in their environment? and (d) Should restraints be used if the patient requests to be restrained? The patients were assessed according to the Temperament and character inventory and Positive and Negative Symptom Scale. Fiftyfour forensic patients with a history of serious offences were included in the study. Their average age was 44.7 (± 8.39) years and the mean duration of their treatment was 6.6 (± 5.08) years. There was no predominant opinion on sharing the information with the family, but there was a relationship between the opinions and psychopathology and personality. Regardless of the patients’ mental state and personality, the opinions on the voluntary use of restraints and the use of restraints as punishment for intentionally aggressive behavior were mainly positive. The patients’ opinions suggest a need for the implementation of more specific guidelines in the area of forensic psychiatry.